The Impact of Civil war on the Balakayati and Warte Region 1993-2000 (Raparin Journal of Humanities (RJH), 2023)
Balakayati and Warte region, an area of a considerable magnitude, It is located in northeastern part of Hawler province. Throughout the latter part of the nineties of twentieth century, the region had become the battleground of civil war between the political parties of Southern Kurdistan. Those wars have left a profound and lasting negative economic, societal, and educational impact. Which tens of people were killed and the social contacts were hugely damaged. On the other hand, Internal wars and conflicts had extermly impacted on education and health sectors, and led to poverty and destruction. It is worth mentioniy thet, this topic is neglected by history researchers. Therefore we decided to conduct research on this significant issue. This research paper includes an overview about Balakayaty and Werte, moreover two sections connected to economical and social negative impacts on the district.